2012
DOI: 10.1002/app.38210
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun polyacrylonitrile nanofibers modified by quaternary ammonium salts

Abstract: Electrospinning from a capillary is one of the methods for the production of nanofibers. The specific properties of such fibers result first of all from their large specific surface and the high porosity of the fiber mat. This article presents a process for producing functional nanofibers with antimicrobiological properties by electrospinning from polyacrylonitrile/dimethyl sulphoxide solution containing a bioactive agent based on quaternary ammonium salts (N, N, n, n,-didecyl-N,N-dimethylammonium chloride, Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 57 publications
5
15
0
Order By: Relevance
“…Sustained broad-spectrum antimicrobial activity is desirable for optimal wound healing because complex tissue interactions between cells, extracellular matrix molecules and soluble mediators are involved in the regeneration of damaged skin or other tissues. Previous studies reported addition of small molecule QACs such as benzalkonium chloride, N,N,n,n,didecyl-N,N-dimethylammonium chloride to polymer solutions for electrospinning of antibacterial nanofibers [306,307]. Such methods suffer from drawbacks such as reduction in fiber diameter and a burst release of QACs.…”
Section: Sutures and Wound Dressingsmentioning
confidence: 99%
“…Sustained broad-spectrum antimicrobial activity is desirable for optimal wound healing because complex tissue interactions between cells, extracellular matrix molecules and soluble mediators are involved in the regeneration of damaged skin or other tissues. Previous studies reported addition of small molecule QACs such as benzalkonium chloride, N,N,n,n,didecyl-N,N-dimethylammonium chloride to polymer solutions for electrospinning of antibacterial nanofibers [306,307]. Such methods suffer from drawbacks such as reduction in fiber diameter and a burst release of QACs.…”
Section: Sutures and Wound Dressingsmentioning
confidence: 99%
“…Several researchers have selected QACs as antimicrobial agents because they had a broad spectrum of antimicrobial activity and could be easily electrospun with PVA polymers [28,38,42]. Benzyl triethylammonium chloride (BTEAC) is a one example of QACs [44]. Some researchers have incorporated BTEAC into polymer solution in order to change the electrical conductivity and surface tension of the solution and to increase spinnability during the electrospinning of nanofibers [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…As the overall physical properties of the resulting materials are strongly controlled by the diameter/thickness of each nanofiber strand and/or the presence of additives (e.g., fillers), finding the optimum electrospinning conditions without disturbing their original structures is always challenging . Recently, hydrophilic polyacrylonitrile (PAN) was electrospun to form nanofiber‐based membranes for water purification because it often serves as a raw material in manufacturing carbon‐based fibers . In addition, the PAN material is relatively easy to handle, and regulating the porosity and pore size of the resulting membranes can be simply tuned by controlling the electrospinning conditions.…”
Section: Introductionmentioning
confidence: 99%